IMMUNOTHERAPY EFFICIENCY IN RHINOSINUSITIS PATIENTS - I. V. Stagnieva; A. S. Simbirtsev (Медицинская иммунология, 2015)
Latent rhinosinusitis proceeds without facial pain symptoms. Immune deficiency plays a leading role in pathogenesis of the disease latency. Substance P seems to be a universal mediator of painful irritation and inflammation. The objective of our study was to determine effectiveness of therapies in patients with latent rhinosinusitis, in terms of substance P levels.We treated 148 patients with rhinosinusitis, being free of local pains. All the patients underwent clinical and laboratory examination, including immune profile assessment, measurements of serum cytokines IL-1β, IL-4, IL-6, IL-8, IL-10, TNFα, IFNγ, and substance P. To correct a secondary immunodeficiency, the standard treatment of rhinosinusitis in a subgroup of the patients was accomplished by immunomodulatory drugs from the first day of therapy. The latter drugs were avoided for the rest of study group. Efficacy of treatment was evaluated by clinical signs and laboratory parameters on day 7 of the medication. Pre-treatment levels of substance P were determined in all the patients with latent clinical course and lack of pain symptoms. Low substance P levels (< 100 pg /ml) were considered as indications for immunomodulatory therapy, due to immune deficiency confirmed by the cytokine imbalance. Choice of a specific drug was dependent on immunopathogenesis, i.e., for catarrhal rhinosinusitis and deficiency of cellular immunity, we administered IFN-ES-lipint; in cases of purulent rhinosinusitis, Likopid was applied. The patients treated with immunomodulatory drugs showed improvement of immune indexes by the 7th day of treatment, along with return of substance P levels to control values typical to healthy persons. Among patients with low substance P levels and immune deficiency (without immunomodulatory treatment), the immune parameters and substance P levels did not exhibit any sufficient changes over time.Low contents of substance P (SP ≤ 100 pg /ml) in blood serum in pain-free patients with latent rhinosinusitis are indicative of immune deficiency and may serve as an indication for immune modulation therapy. Individual selection of the pathogenetically proven schedule therapy, when treating patients with latent (painless) rhinosinusitis may result into effective prevention of severe inflammation, normalization of immune response, prevention of a protracted disease course, and appropriate complications, as well as shortening of treatment terms to 8-10 days